COUNTERREENGINEERING OF ELECTRONIC DEVICES - M. S. Kostin; D. S. Vorunichev; D. A. Korzh (Российский технологический журнал)
The paper presents the main results of scientific and practical research in the field of special design reengineering and counterreengineering of radioelectronic devices. Methods and means of special design reengineering of functional modules of multilayer printed circuit boards and case microcircuits are presented. The basic process design for the reengineering of multilayer printed circuits of radioelectronic products is presented. The design is based on the physical principles of destructive and non-destructive decomposing test: mechanical processing and chemical etching, stereolaser structuring, IR imaging electrothermics and X-ray analysis. The article formulates positions and methodology of the circuit analysis of the basic architecture of electrical circuits and signal processes of radio electronic products by the configuration of the printed circuit, its electronic component base and their connected topologies. The article considers methods and techniques for the reengineering of radiotechnical circuits and signals enabling to reproduce the list of the electronic component base and the essential circuit technique, as well as to study the basic circuit characteristics of the appliance in four main modes: functional, in-circuit, peripheral and identification visualization. The methods and means of authentic performance of radioelectronic devices for a number of constructive and radiotechnical identifiers are considered. Technical methods and solutions for counterreengineering of radioelectronic devices have been developed.